AKSI MASYARAKAT MENJAGA IMUNITAS TUBUH DAN BERBAGI JAHE DI KECAMATAN TAMBUN SELATAN - Nusantara, Dimas Taruna; Ridlo, Azi Fais; Iskandar, Tatang (DEVOSI, 2022)
The body's immune system is the most important thing to maintain a person's health to avoid Covid-19. Many people ignore their immunity in Tambun Selatan sub-district. In this activity, the author uses the method of conducting online webinar with descriptive analysis techniques. he activity plan is carried out by creating a whatsapp group first, then participants fill out the pre-test, and participate in webinar activities, followed by filling out the post-test, and ending with evaluation and follow-up activities. From the results of the webinar activity, 9 people felt very satisfied (45%), 10 people felt satisfied (50%), 1 person felt dissatisfied (5%) so that revalance can help people's knowledge.